Comparison of PCR, Culture, and Direct Fluorescent-Antibody Testing for Detection of Bordetella pertussis - Loeffelholz, Mike J. (American Society for Microbiology, 1999)
We prospectively compared the performance of culture, direct fluorescent-antibody testing (DFA), and an in-house-developed PCR test targeting the repeated insertion sequence IS481 for the detection of Bordetella pertussis in nasopharyngeal swab specimens. We tested 319 consecutive paired specimens on which all three tests were performed. A total of 59 specimens were positive by one or more tests. Of these, 5 were positive by all three tests, 2 were positive by culture and PCR, 16 were positive by PCR and DFA, 28 were positive by PCR only, and 8 were positive by DFA only. Any specimen positive by culture was considered to be a true positive, as were specimens positive by both PCR and DFA. Specimens positive only by PCR or DFA were considered discrepant, and their status was resolved by review of patient histories. Patients with symptoms meeting the Centers for Disease Control and Prevention clinical case definition for pertussis and who had a specimen positive by PCR or DFA were considered to have true B. pertussis infections. Of the 28 patients positive by PCR only, 20 met the clinical case definition for pertussis, while 3 of the 8 patients positive by DFA only met the clinical case definition. After resolution of the status of discrepant specimens, the sensitivity, specificity, positive predictive value, and negative predictive value were 15.2, 100, 100, and 87.5%, respectively, for culture; 93.5, 97.1, 84.3, and 98.9%, respectively, for PCR; and 52.2, 98.2, 82.8, and 92.4%, respectively, for DFA. The actual positive predictive value of PCR was probably greater, as several PCR-positive patients who did not meet the clinical case definition had symptoms consistent with typical or atypical pertussis. PCR is a sensitive and specific method for the detection of B. pertussis.